If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + -15 = 2x + 6 Reorder the terms: -15 + 5c = 2x + 6 Reorder the terms: -15 + 5c = 6 + 2x Solving -15 + 5c = 6 + 2x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5c = 6 + 15 + 2x Combine like terms: -15 + 15 = 0 0 + 5c = 6 + 15 + 2x 5c = 6 + 15 + 2x Combine like terms: 6 + 15 = 21 5c = 21 + 2x Divide each side by '5'. c = 4.2 + 0.4x Simplifying c = 4.2 + 0.4x
| p^2+10p-104=-8 | | 5+8m-4=5m+16-2m | | t^3-3r^2-10t=0 | | (2x-4i)(x-2i)=0 | | 3q-(-6)=12 | | 2y*27=5y | | 60y-4=173 | | n^2-16n-24=-8 | | 2.3x+34.7=3.8-8.0x | | 7c=2v-20 | | 6x+24+2=-4+-28 | | 5x-8=5y | | (x+5)(x-18)=0 | | -2[4-(3b+2)]=4-2(3b+9) | | 48-31w=-18 | | x+2x+x+3=30 | | 6x+2x+x+3= | | w^2-13w-36=0 | | 4-3x=42 | | 22(2x+y)=29 | | w=.28w+48 | | 2/3x-0,7=1,3x+2 | | -3125=r^5 | | 6x^2+9x-36=0 | | 6x+=20 | | 5sinx+4=3sinx+3 | | f(x)=2x^2+16x+5 | | 3(x-1)+6=-6x(x+7) | | 5(2w-7)=65 | | -4x+3y+15=0 | | 7x-92=252 | | T+10=7t-13 |